Comparison of a low-glycemic index vs standard diabetic diet - Visek, Jakub; Lacigova, Silvie; Cechurova, Daniela; Rusavy, Zdenek (Biomedical papers, 2014)
Aim: There is insufficient evidence for the efficacy of a low-glycemic index (GI) diet in the management of diabetes. The goal of this study was to measure the effect of a low GI versus a standard diabetic diet in adults with diabetes type 2.Methods: This was an open label, randomized, crossover study. Twenty persons with type 2 diabetes were randomized to two groups. Each group followed a standard diabetic diet or a low glycemic index diet for 3 months. The effectiveness of the two diets was evaluated using a hyperinsulinemic euglycemic clamp with endogenous glucose production measurement, indirect calorimetry and bioimpedance analysis. Outcome measures were body mass, BMI, body fat, glycosylated hemoglobin, fasting glucose, lipid profile, insulin sensitivity and hepatic glucose production.Results: Body mass after 3 months following the diabetic diet was 93 kg (83-104) vs. low glycemic index diet 92 kg (85-104) P<0.05, BMI 31.3 kg/m2 (27.5-35.9) vs. 30.7 kg/m2 (27-35.3) P<0.05, body fat 28% (25.5-43) vs. 27% (23-43) P<0.05 (median and interquartile range). There was no statistically significant difference between diets for glycosylated hemoglobin, fasting glucose, lipid profile, insulin sensitivity or hepatic glucose production.Conclusions: The results are comparable with other studies showing a modest effect of a low GI diet in the management of diabetes. We found a modestly greater weight loss, body fat and BMI reduction on the low GI diet.
Keywords: diabetes type 2; low glycemic index diet; standard diabetic diet; hepatic glucose production